Detection of Pseudomonas syringae pv. Syringae In pea seed - and K.R. SHYAM, R. CHOPRA, K.K. JINDAL (Indian Phytopathology, 2002)
Among the three tests tried, wounded growing on test was found best for the detection of Pseudomonas syringae pv. syringae, the incitant of bacterial blight disease in pea. In a seed lot categorised into three categories i.e., apparently healthy, deformed (including small and shrivelled) and discoloured (seeds having brown crust and water soaked deep green spots) maximum .number of diseased seedlings developed from deformed seeds followed by discoloured ones. Diseased seedlings also developed from the apparently healthy seed lot. Traditional growing on test also proved quite successful in the month of April, when the conditions were favourable (mean 20Â°C) for the manifestation of disease symptoms. It met with limited success in the month of June when the temperature was quite high i.e., mean 26Â°C. Incubation growing on test proved superior to traditional growing on test. The seed infestation to the extent of 0.1 per cent could be detected by wounded seed growing on test only.